1985
DOI: 10.1111/j.1469-7998.1985.tb03547.x
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of a Mediterranean tortoise (Testudo hermanni): Reproduction

Abstract: A three‐year study on reproduction in wild populations of Testudo hermanni has shown that: (a) sexual activity occurs between March and October, except the nesting season (May and June), and is most frequent in August and September, (b) tortoises are promiscuous in their mating habits, there is no evidence of mate selection in relation to size, (c) nest site selection is correlated to ground temperature and nesting itself mainly occurs in the early evening before dark, when the ground temperature characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 17 publications
1
15
0
3
Order By: Relevance
“…We focused on the relationships between the flagship species T. hermanni and the coastal EU habitats. Our results confirmed that climate and behavioral patterns play a crucial role in habitat use and preference by ectothermic species, especially tortoises [15,16,21,[47][48][49][50][51]. Hermann's tortoise broadly selected patchy areas [21] where close vegetation alternates with open areas with a specific seasonal pattern that was assessed here for the first time.…”
Section: Final Remarks and Conservation Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…We focused on the relationships between the flagship species T. hermanni and the coastal EU habitats. Our results confirmed that climate and behavioral patterns play a crucial role in habitat use and preference by ectothermic species, especially tortoises [15,16,21,[47][48][49][50][51]. Hermann's tortoise broadly selected patchy areas [21] where close vegetation alternates with open areas with a specific seasonal pattern that was assessed here for the first time.…”
Section: Final Remarks and Conservation Implicationssupporting
confidence: 88%
“…The need to escape the high summer temperatures at the onset of the pre-estivation phase [14][15][16]47,48] is the main factor that most likely influenced the exclusive preference for the close vegetation of sclerophyllous scrubs (EU cod. 2260) observed in July.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Swingland & Stubbs (1985), a vulnerabilidade dos ninhos à predação, o sucesso da eclosão e o sexo dos recém-eclodidos são todos dependentes da seleção do local de desova. Diversos fatores podem influenciar a taxa de predação, dentre os quais, o ambiente de nidificação, a disponibilidade de predadores e as características e a densidade das covas (Burger, 1976;Burke et al, 1998;Pezzuti & Vogt, 1999;Ferreira Jr., 2003).…”
Section: Predação De Ovos E Filhotesunclassified
“…Segundo Swingland & Stubbs (1985) os jabutis gigantes (Geochelone gigantea e Geochelone elefhantopus) possuem apenas um predador de ninhos, um grande caranguejo terrestre (Birgus latro).…”
Section: Predação De Ovos E Filhotesunclassified
See 1 more Smart Citation